Common understanding on international standards and gateways for central securities depository and real time gross settlement (csd-rtgs) linkages. (Southeast Asia working papers., 2019)
Prepared for the Cross-Border Settlement Infrastructure Forum (CSIF) to support its efforts to establish central securities depository and real-time gross settlement linkages. Aims to build a common understanding among CSIF members about international standards and gateways for these linkages.